Vulcanized rubber composition for studless tire, and studless tire
Patent Information
- Application Number
- JP2023142534
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0015】 本発明によれば、ゴム組成物の加工性や作業性を良好に維持しつつ、タイヤのWet性能及サステナブル材料比率を向上させることが可能なスタッドレス用加硫ゴム組成物を提供することができる。 また、本発明によれば、生産性と性能を維持しつつ、Wet性能及びサステナブル材料比率を向上させたスタッドレスタイヤを提供することもできる。
Smart Images

Figure 2025035476000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a vulcanized rubber composition for studless tires and a studless tire. [Background technology]
[0002] In general, natural rubber is known as a rubber with excellent mechanical properties and abrasion resistance. Such natural rubber is obtained by collecting natural rubber latex and going through the steps of coagulation, maturation as necessary, washing, dehydration, drying, and packing in that order. The natural rubber is masticated, mixed with compounding ingredients, molded, and vulcanized to produce the desired rubber product. Natural rubber latex contains non-rubber components such as proteins, lipids, sugars, and inorganic substances in addition to the rubber content of about 25 to 35% w / v (weight / volume), and natural rubber obtained by coagulating it with formic acid or the like contains about 6% by mass of non-rubber components. Although these non-rubber components have anti-aging effects and vulcanization-accelerating effects, highly polar compounds such as proteins have been found to be components that deteriorate the processability and heat generation of vulcanized rubber.
[0003] Therefore, for example, Patent Document 1 discloses a method for producing natural rubber in which, in order to improve low heat build-up properties without impairing aging resistance, proteins contained in the non-rubber components of natural rubber latex are subjected to partial deproteinization treatment using only mechanical separation means using centrifugation so that the total nitrogen content in the solid components of the natural rubber latex is more than 0.1% by mass and not more than 0.4% by mass, and then coagulation and drying treatments are performed. Furthermore, Patent Document 2 discloses natural rubber having a phosphorus content of 200 ppm or less, and a method for producing the same, in which natural rubber latex is saponified with an alkali, the rubber coagulated after saponification is washed, and then dried, from the viewpoint that it is preferable that natural rubber is substantially free of phospholipids, taking into consideration the processability of natural rubber. However, the natural rubbers obtained by the techniques of Patent Documents 1 and 2 both left room for further improvement in terms of processability and workability during production (hereinafter simply referred to as "workability").
[0004] Meanwhile, apart from improving the processability and low heat generation properties of natural rubber mentioned above, research is being conducted particularly on tire treads in order to improve the braking and driving performance of tires on wet roads (hereinafter referred to as "wet performance"). The water film that forms on a wet road surface reduces the coefficient of friction between the tire and the road surface. Therefore, in order to improve the wet performance of tires, it is necessary to improve the water film removal ability of the tire tread, as well as the edge effect and spike effect. For example, it is known that in order to impart water film removal capability to a tire tread, micro drainage grooves are provided on the road surface of the tire, and these micro drainage grooves remove the water film and increase the tire's friction coefficient on icy and snowy road surfaces. However, when micro drainage grooves are provided on the road surface of a tire, although it is possible to improve the tire's performance on ice in the early stages of use, there is a problem that the tire's wear resistance decreases and it is difficult to maintain the performance on ice, and further improvement has been desired.
[0005] Furthermore, in recent years, from the perspective of social sustainability, there has been a demand for the use of so-called sustainable materials, such as materials derived from biological resources (biomass resources) and materials derived from recycled resources, for the various components used in tires, and there is also a desire to develop technology to increase the usage rate of sustainable materials (hereinafter sometimes referred to as the "sustainable material ratio"). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2004-262973 A [Patent Document 2] JP 2010-138359 A Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, an object of the present invention is to provide a vulcanized rubber composition for studless tires that can improve the wet performance and sustainability rate of a tire while maintaining good processability and workability of the rubber composition. Another object of the present invention is to provide a studless tire that has improved wet performance and a sustainable material ratio while maintaining productivity and performance. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to further improve the wet performance and sustainable material ratio of vulcanized rubber compositions for studless tires. They have found that by reducing the nitrogen content in natural rubber to a specific range, high processability and workability can be achieved even when currently used fossil resource-derived materials are replaced with sustainable materials in the rubber composition, and that by providing multiple voids in the vulcanized rubber composition, wet performance can also be improved.
[0009] That is, the gist of the present invention is as follows. [1] A vulcanized rubber composition for studless tires, comprising: The natural rubber is a modified natural rubber having a nitrogen content of 0.1 to 0.3% by mass, The vulcanized rubber composition for studless tires is characterized in that it has a plurality of voids. The vulcanized rubber composition for studless tires of the present invention described in [1] above is capable of improving the wet performance and sustainability rate of tires while maintaining good processability and workability of the rubber composition.
[0010] [2] The vulcanized rubber composition for studless tires described in [1], characterized in that the modified natural rubber has had proteins removed by a centrifugation process, enzyme treatment, or urea treatment. The vulcanized rubber composition for studless tires of the present invention described in [2] above can further improve the processability and workability of the rubber composition.
[0011] [3] The vulcanized rubber composition for studless tires according to [1] or [2], characterized in that the modified natural rubber has a phosphorus content of more than 200 ppm. The vulcanized rubber composition for studless tires of the present invention described in [3] above can further improve abrasion resistance.
[0012] [4] The vulcanized rubber composition for studless tires according to any one of [1] to [3], characterized in that the rubber composition further contains a reinforcing filler. The vulcanized rubber composition for studless tires of the present invention described in [4] above can further improve abrasion resistance and wet performance.
[0013] [5] The vulcanized rubber composition for studless tires according to any one of [1] to [4], wherein the rubber composition further contains a void-introducing agent. The vulcanized rubber composition for studless tires of the present invention described in [5] above can further improve wet performance.
[0014] [6] A studless tire, comprising the vulcanized rubber composition for studless tires according to any one of [1] to [5]. The studless tire of the present invention described in [5] above has high wet performance and sustainability while maintaining productivity and performance. Effect of the Invention
[0015] According to the present invention, it is possible to provide a vulcanized rubber composition for studless tires that can improve the wet performance and sustainable material ratio of a tire while maintaining good processability and workability of the rubber composition. Furthermore, according to the present invention, it is possible to provide a studless tire that has improved wet performance and a sustainable material ratio while maintaining productivity and performance. [Brief description of the drawings]
[0016] [Figure 1]FIG. 2 is a schematic diagram showing a plurality of voids present in a vulcanized rubber composition according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a cross section of a void present in a vulcanized rubber composition according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described with reference to the drawings as necessary. The compounds described in this specification may be derived partially or entirely from fossil resources, from biological resources such as plant resources, or from recycled resources such as used tires, or may be derived from a mixture of two or more of fossil resources, biological resources, and recycled resources.
[0018] In addition, in this specification, the "sustainable rate" refers to the total mass ratio of components derived from biological resources (biomass resources) and components derived from renewable resources (recycled resources) in the target material, and is also referred to as the "sustainable material ratio."
[0019] In this specification, the biological resources (biomass resources) refer to carbon-neutral organic resources derived from living organisms, and include, for example, those stored in the form of starch or cellulose, the bodies of animals that grow by eating plants, and products obtained by processing plants or animals, and are resources other than fossil resources (petroleum, coal, natural gas, etc.). The biological resources may be edible or non-edible, but are preferably non-edible from the viewpoint of not competing with food and of effective resource utilization.
[0020] Specific examples of the biological resources include cellulosic crops (pulp, kenaf, wheat straw, rice straw, waste paper, papermaking residues, etc.), wood, charcoal, compost, food waste, vegetable oil residues, fishery residues, livestock waste, food waste, wastewater sludge, natural rubber, cotton, oils and fats (palm oil, castor oil, cottonseed oil, soybean oil, linseed oil, rapeseed oil, coconut oil, peanut oil, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive ... Examples of the biological resources include crops (corn, wheat, rice, rice husks, rice bran, old rice, potatoes, buckwheat, cassava, sago palm, sugarcane, etc.), bagasse (i.e., the residue after squeezing juice from sugarcane), soybeans, soybean pulp, essential oils (pine oil, orange oil, eucalyptus oil, etc.), pulp black liquor, algae, etc. The biological resources may be processed (i.e., biological resource-derived substances). Examples of the processing methods include biological processing methods that utilize the functions of microorganisms, plants, animals, and tissue cultures thereof; chemical processing methods that utilize acids, alkalis, catalysts, thermal energy, light energy, etc.; physical processing methods such as micronization, compression, microwave processing, and electromagnetic wave processing; and the like. The biological resources may also be extracted and refined from the biological resources or biological resources that have been processed (i.e., biological resource-derived substances). For example, sugars, proteins, amino acids, fatty acids, fatty acid esters, etc., purified from the biological resources can be used. Examples of the sugars include sucrose, glucose, trehalose, fructose, lactose, galactose, xylose, allose, talose, gulose, altrose, mannose, idose, arabinose, apiose, maltose, cellulose, starch, chitin, etc., derived from biological resources. Examples of the proteins include compounds derived from biological resources and formed by linking amino acids (preferably L-amino acids), including oligopeptides such as dipeptides. Examples of the amino acids include valine, leucine, isoleucine, arginine, lysine, asparagine, glutamine, phenylalanine, etc., derived from biological resources, and among these, valine, leucine, isoleucine, arginine, and phenylalanine are preferred.The amino acid may be either an L-amino acid or a D-amino acid, but L-amino acids are preferred from the viewpoints of abundance in nature and ease of availability. The fatty acids include butyric acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, etc., which are derived from biological resources. The fatty acid esters include modified products of vegetable oils, animal oils, and fats and oils derived from biological resources. These biological resources may be contaminated with various materials and impurities.
[0021] In this specification, the term "recycled resources" refers to resources obtained by regenerating (recycling) products that have been used once, or that have been collected without being used, or that have been discarded. For example, recycled resources include resources obtained by regenerating (recycling) used rubber products such as used tires.
[0022] <Vulcanized rubber composition for studless tires> The vulcanized rubber composition for studless tires of the present invention is a vulcanized rubber composition for studless tires obtained by vulcanizing a rubber composition containing natural rubber, The natural rubber is a modified natural rubber having a nitrogen content of 0.1 to 0.3% by mass, The vulcanized rubber composition has a plurality of voids.
[0023] In the vulcanized rubber composition for studless tires of the present invention, the nitrogen content in the natural rubber is reduced to 0.1 to 0.3 mass %, making it possible to achieve high processability and workability even when the fossil resource-derived material (synthetic rubber) currently used in the rubber composition is replaced with a sustainable material (natural rubber).
[0024] In addition, the vulcanized rubber composition 10 for studless tires of the present invention has a plurality of voids 20 as shown in FIG. 1, and therefore, when applied to a tire, the wet performance can be improved.
[0025] Here, the voids in the vulcanized rubber composition for studless tires of the present invention refer to holes having an average diameter of about 1 to 500 μm formed in the vulcanized rubber composition for studless tires as shown in Fig. 1. Here, the diameter of the voids refers to the largest diameter D of the void 20 as shown in Fig. 2 (when the void is not spherical, the largest distance D among the distances between any two points on the inner wall of the void). The average diameter of the voids is the average value of the diameter D of the voids 20 present in the vulcanized rubber composition for studless tires of the present invention. In the present invention, the cross section of the vulcanized rubber composition for studless tires is observed with a digital microscope ("VHX-100" manufactured by Keyence Corporation), and the average value of the diameters of all the voids present in one field of view (2.5 mm x 2.5 mm) is used. In the vulcanized rubber composition for studless tires of the present invention, the shape and size of the voids do not vary significantly within one vulcanized rubber composition for studless tires, so the average value of the voids in one field of view can be used as the average diameter of the voids.
[0026] Moreover, the porosity of the vulcanized rubber composition for studless tires of the present invention is preferably 5 to 45%. By setting the lower limit of the porosity to 5%, the wet performance can be improved more reliably. From the same viewpoint, the porosity is preferably 7% or more, and more preferably 15% or more. On the other hand, by setting the upper limit of the porosity to 45%, even in the case of having a plurality of voids, the deterioration of the abrasion resistance can be more reliably suppressed. From the same viewpoint, the porosity is preferably 40% or less, and more preferably 37% or less. The void ratio is the ratio (volume %) of the volume of the voids in the vulcanized rubber composition for studless tires of the present invention. The method for measuring the void ratio is not particularly limited, and can be measured, for example, using a specific gravity meter (ViBRA specific gravity meter "DMA-220" manufactured by Shinko Denshi Co., Ltd.).
[0027] Here, the vulcanized rubber composition for studless tires of the present invention has a plurality of voids, but the method for providing the voids is not particularly limited. The voids can be formed using known techniques depending on the void conditions and the equipment for producing the vulcanized rubber composition for studless tires. For example, as described below, a method can be used in which voids are provided in the vulcanized rubber composition for studless tires by blending a foaming agent, a foaming aid, composite fibers, etc., into the rubber composition before vulcanization. The void ratio can be controlled by changing the vulcanization conditions or by adjusting the content of a void-introducing agent such as a foaming agent or composite fibers. As a method for providing the voids, a technique can be used in which powdered rubber is blended into the rubber composition before vulcanization, so that the powdered rubber falls off from the surface of the rubber composition after vulcanization, forming voids near the surface of the vulcanized rubber composition for studless tires. In this case, it is possible to adjust the size of the voids, the porosity, and other conditions by adjusting the particle size and number of the powdered rubber.
[0028] The vulcanized rubber composition for studless tires is a vulcanized rubber obtained by vulcanizing an unvulcanized rubber composition. The vulcanization conditions (temperature, time) are not particularly limited, and the vulcanization process can be performed under any conditions depending on the required performance.
[0029] The unvulcanized rubber composition (hereinafter simply referred to as "rubber composition") that is the base of the vulcanized rubber composition for studless tires of the present invention will be described below. The rubber composition contains at least natural rubber. Each component constituting the rubber composition will be described below.
[0030] (Rubber component) Modified natural rubber The rubber component contained in the rubber composition contains at least a modified natural rubber having a nitrogen content of 0.1 to 0.3 mass % (hereinafter simply referred to as "modified natural rubber"). By including the above-mentioned modified natural rubber as the rubber component, the natural rubber does not contain an excessive amount of protein and gelation is suppressed, thereby improving processability and workability, and the interaction between polymers in the natural rubber is promoted, thereby improving abrasion resistance and low heat generation. From the same viewpoint, the nitrogen content in the modified natural rubber is preferably 0.15% by mass or more and 0.25% by mass or less.
[0031] The modified natural rubber preferably has a long chain branching index (LCB Index) of 3.0 or more and 5.5 or less at 70°C, and a long chain branching index (LCB Index) of 2.0 or more and 4.0 or less at 130°C, based on the following formula (I): LCB Index=G'1 / G'5...(I) The long chain branching index (LCB Index) can be measured by the LAOS measurement method using an RPA2000 type tester (manufactured by Alpha Technologies). The long chain branching index (LCB Index) measured by the LAOS measurement method using an RPA2000 type tester (manufactured by Alpha Technologies) is a more accurate index of long chain branching that removes the influence of molecular weight distribution from the behavior of long chain branching (LCB) and molecular weight distribution, which have similar characteristics in the dynamic properties of dissolved polymers. For details on LAOS for determining the LCB Index, please refer to "FT-Rheology, a Tool to Quantify Long Chain Branching (LCB) in Natural Rubber and its Effect on Mastication, Mixing Behaviour and Final Properties" (Henri G. Burhin, Alpha Technologies, UK 15 Rue du Culot B-1435 Hevillers, Belgium), etc. Here, LAOS stands for Large Amplitude Oscillatory Shear. In this specification, the shear stress signal obtained by measurement in LAOS mode using an RPA2000 testing machine (manufactured by Alpha Technologies) is calculated by discrete Fourier transform up to n = 1 to 9 (n is an integer), (In the formula, γ0: amplitude, t: time, ω: angular velocity (unit: rad / s)) The shear stress τ is fitted to the equation: Furthermore, using the τ calculated from the above formula, the test specimen with a mass of 5g was subjected to the following measurement conditions: pressure during measurement was 15.6kN, temperature was 70°C, frequency was 1.67Hz, strain was 0.5%, and the specimen was left for 1 minute. Then, over 10 seconds (i.e., 0.1Hz), the angular velocity ω was set to 0.50 rad / s, the angle was 71.5 degrees, strain was 1000%, and the pressure during measurement was 15.6kN. The temperature was then increased successively to 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, and 130°C, and G'n was calculated at each temperature. The long chain branching index (LCB Index) at 70°C and 130°C was then calculated from G'1 / G'5. In the examples, the measurements were carried out in the same manner as above.
[0032] The long-chain branching index (LCB index) at 70°C measured by the above-mentioned LAOS measurement method indicates the amount of branches containing weak bonds (i.e., hydrogen bonds, etc.) in the branched structure of natural rubber, while the long-chain branching index (LCB index) at 130°C indicates the amount of branches due to strong bonds (i.e., covalent bonds) in the branched structure of natural rubber.
[0033] The modified natural rubber preferably has a long chain branching index (LCB Index) at 70°C of 3.0 or more and 5.5 or less, more preferably 3.5 or more and 5.2 or less, even more preferably 3.0 or more and 5.1 or less, and particularly preferably 4.0 or more and 5.0 or less, and preferably has a long chain branching index (LCB Index) at 130°C of 2.0 or more and 4.0 or less, more preferably 2.0 or more and 3.5 or less, even more preferably 2.0 or more and 3.0 or less, even more preferably 2.0 or more and 2.8 or less, and particularly preferably 2.0 or more and 2.5 or less.
[0034] Since the modified natural rubber has long chain branching indices within the above ranges at both 70°C and 130°C, the amount of branching due to both bonds in the natural rubber is reduced, resulting in a dramatic improvement in the processability of the natural rubber compared to conventional methods. Furthermore, the natural rubber of the present invention in which the amount of branching due to both bonds is reduced provides high dispersibility of fillers such as carbon black when producing pneumatic tires, for example, and therefore improves the wear resistance of the tires.
[0035] Furthermore, the phosphorus content in the modified natural rubber is preferably more than 200 ppm, and is preferably 900 ppm or less, and more preferably 700 ppm or less. When the modified natural rubber has a phosphorus content within the above range, interaction between polymers in the natural rubber is promoted to increase the molecular weight, thereby improving the abrasion resistance.
[0036] The method for producing the modified natural rubber is not particularly limited. For example, the proteins can be removed by a centrifugation process, enzyme treatment or urea treatment to obtain the modified natural rubber.
[0037] The centrifugation process is a process for deproteinizing natural rubber latex, which is the raw material of natural rubber, by centrifugation. The conditions for the centrifugation (rotation speed, time, etc.) are not particularly limited, and the conditions can be appropriately changed depending on the protein content to be removed. For example, when the nitrogen content in natural rubber is to be 0.1 mass% or less, the centrifugation process can be carried out several times at a rotation speed of about 7500 rpm. After the centrifugation process, washing and drying processes are carried out to obtain highly purified natural rubber.
[0038] The enzyme treatment is a treatment for selectively decomposing proteins in natural rubber latex, which is a raw material for natural rubber. The enzyme used in the enzyme treatment is not particularly limited as long as it is an enzyme that can decompose proteins, and examples thereof include proteases.
[0039] Proteases can be classified according to the location of degradation, for example, into exopeptidases (which cut off approximately 1 to 2 amino acid residues from the ends of protein / peptide chain sequences) and endopeptidases (which cut in the center of protein / peptide chain sequences). In terms of classification by substrate, examples include proteinases (which break down proteins) and (in the narrow sense) peptidases (which break down synthetic peptides with smaller molecular weights). Furthermore, from the perspective of classification based on catalytic mechanism, these include serine proteases such as chymotrypsin and subtilisin; aspartic acid proteases (acid proteases) such as pepsin, cathepsin D, and HIV protease; metalloproteases such as thermolysin; cysteine proteases such as papain and caspases; and N-terminal threonine proteases and glutamic acid proteases, which are now known to occur in the proteasome. Furthermore, in the enzyme treatment, it is preferable to use an endopeptidase from the viewpoint of the decomposition site. In addition, a protease that is highly active at about pH 10.5 when ammonia is added, i.e., an alkaline protease, is preferable, and from the viewpoint of suppressing the coagulation of natural rubber latex, a protease that is highly active at an optimum temperature of 10 to 40°C, preferably at about room temperature (e.g., 20°C) is preferable. The protease may be one of the above-mentioned types, or may be a composition containing two or more of the above-mentioned types. Furthermore, the protease may be a main component containing an enzyme other than the protease, or a main component other than the protease may contain the protease as a side activity.
[0040] The urea treatment is a process in which proteins in natural rubber latex, the raw material of natural rubber, are denatured with a urea-based compound and then removed. The urea-based compound here refers to urea derivatives and urea complex salts.
[0041] Examples of the urea derivative include urea, methylurea, ethylurea, n-propylurea, i-propylurea, n-butylurea, i-butylurea, and n-pentylurea, and preferred urea derivatives include urea, methylurea, and ethylurea. Examples of the urea complex salt include HNO3·CO(NH2)2, H3PO4·CO(NH2)2, H2C2O4·2CO(NH2)2, Ca(NO3)2·4CO(NH2)2, CaSO4·4CO(NH2)2, Mg(NO3)2·CO(NH2)2·2H2O, CaSO4·(5-6)CO(NH2)2·2H2O, etc.
[0042] The natural rubber latex which has been subjected to the urea treatment is then subjected to separation and removal treatment of the natural rubber and proteins by means of mechanical separation, coagulation of the rubber component, ultrafiltration, etc. The natural rubber latex which has been subjected to the protein modification treatment is refined by such removal treatment to produce highly purified natural rubber.
[0043] The natural rubber latex used in the centrifugation process, enzyme treatment, or urea treatment is not particularly limited. For example, field latex collected from rubber trees or concentrated natural rubber latex obtained by treating the field latex may be used. The dry rubber content in the natural rubber latex is also not particularly limited, and from the viewpoint of obtaining better abrasion resistance, it is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more.
[0044] The content of the modified natural rubber in the rubber component may be 100%, but other rubbers may also be contained within a range that does not impair the object of the present invention. Furthermore, the natural rubber may be not only the highly purified natural rubber, but also a mixture with ordinary natural rubber. However, even in this case, the nitrogen content of the entire natural rubber must be 0.1 to 0.3 mass% (the entire natural rubber becomes a modified natural rubber having a nitrogen content of 0.1 to 0.3 mass%). In this case, the content of the modified natural rubber in the rubber component is preferably 10% by mass or more, more preferably 20 to 90% by mass, and particularly preferably 40 to 70% by mass, from the viewpoint of further improving the sustainable material ratio and abrasion resistance.
[0045] Rubber components other than modified natural rubber As described above, the rubber component may contain rubber components other than the modified natural rubber (hereinafter, sometimes referred to as "other rubber components"). The other rubber components are preferably the rubber derived from biological resources and the rubber derived from recycled resources. Here, the proportion of the monomer components derived from biological resources in 100 mol% of the monomer components constituting the rubber derived from biological resources is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, still more preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be 100 mol%. Furthermore, the proportion of monomer components derived from recycled resources in 100 mol% of monomer components constituting the rubber derived from recycled resources is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, still more preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be 100 mol%.
[0046] The other rubber components are components that contribute to crosslinking, and usually have a weight average molecular weight (Mw) of 10,000 or more, preferably 50,000 or more, more preferably 150,000 or more, and even more preferably 200,000 or more, and preferably 5 million or less, more preferably 2 million or less, more preferably 1.5 million or less, and even more preferably 1.3 million or less. The weight average molecular weight (Mw) of the rubber component can be determined, for example, by converting the measured value into that of standard polystyrene using a gel permeation chromatograph (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M manufactured by Tosoh Corporation).
[0047] The other rubber component is preferably a diene rubber, and the diene rubber is preferably an isoprene rubber or a butadiene rubber, where the isoprene rubber refers to a rubber containing units derived from isoprene as a monomer unit, and the butadiene rubber refers to a rubber containing units derived from butadiene as a monomer unit.
[0048] Examples of the isoprene-based rubber include natural rubber (NR) other than the modified natural rubber, synthetic isoprene rubber (IR), modified natural rubber (modified NR), modified natural rubber (modified NR), modified synthetic isoprene rubber (modified IR), etc. Natural rubber (NR) that is common in the tire industry, such as SIR20, RSS#3, TSR20, etc., can be used. The origin of the natural rubber (NR) is not particularly limited, and examples of the natural rubber include those derived from Hevea brasiliensis, guayule, and Russian dandelion. Synthetic isoprene rubber (IR) is not particularly limited, and examples of the synthetic isoprene rubber that is common in the tire industry, such as IR2200, can be used. Examples of modified NR include deproteinized natural rubber (DPNR), high-purity natural rubber (UPNR), etc. Examples of modified NR include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. The modified IR includes epoxidized synthetic isoprene rubber, hydrogenated synthetic isoprene rubber, grafted synthetic isoprene rubber, etc. These isoprene-based rubbers may be used alone or in combination of two or more. Among these, NR is preferred as the isoprene-based rubber.
[0049] The isoprene-based rubber preferably has a sustainability rate of 30% by mass or more, more preferably 40% by mass or more, more preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 100% by mass. In order to set the sustainability rate of the isoprene-based rubber within the above range, it is preferable to use natural rubber (NR) or a polymer synthesized using isoprene derived from biological resources or isoprene derived from renewable resources as a monomer component. In this case, the synthesized polymer may be a homopolymer of a monomer derived from biological resources, a homopolymer of a monomer derived from renewable resources, a copolymer of a monomer derived from biological resources and a monomer derived from renewable resources, or a copolymer of a monomer derived from biological resources and / or a monomer derived from renewable resources and a monomer derived from a fossil resource (petroleum, etc.).
[0050] Examples of the butadiene rubber include butadiene rubber (BR), aromatic vinyl compound-butadiene copolymer rubber (for example, styrene-butadiene rubber (SBR)), etc. Here, butadiene, which is a raw material for butadiene rubber, is preferably derived from biological resources or recycled resources.
[0051] Examples of the butadiene rubber (BR) include high cis content butadiene rubber, low cis content butadiene rubber, and butadiene rubber containing syndiotactic polybutadiene crystals. Commercially available products can be used as the butadiene rubber (BR), and examples of commercially available butadiene rubbers include products from UBE Elastomers Co., Ltd., ENEOS Materials Corporation, Asahi Kasei Co., Ltd., and Zeon Corporation. These butadiene rubbers may be used alone or in combination of two or more.
[0052] Examples of the aromatic vinyl compound-butadiene copolymer rubber (e.g., SBR) include emulsion-polymerized aromatic vinyl compound-butadiene copolymer rubber (e.g., emulsion-polymerized styrene-butadiene rubber (E-SBR)), solution-polymerized aromatic vinyl compound-butadiene copolymer rubber (e.g., solution-polymerized styrene-butadiene rubber (S-SBR)), and the like. In the aromatic vinyl compound-butadiene copolymer rubber, examples of the aromatic vinyl compound (aromatic vinyl monomer) include styrene, vinylnaphthalene, divinylnaphthalene, and the like. These aromatic vinyl compounds may be used alone or in combination of two or more. Among these, styrene is preferred, and styrene derived from biological resources and styrene derived from recycled resources are particularly preferred. That is, the aromatic vinyl compound-butadiene copolymer rubber is preferably SBR. The styrene may have a substituent. As the aromatic vinyl compound-butadiene copolymer rubber, commercially available products can be used, and examples of the commercially available products include products from Asahi Kasei Corporation, ENEOS Materials Corporation, Nippon Zeon Corporation, Sumitomo Chemical Co., Ltd., and the like. These aromatic vinyl compound-butadiene copolymer rubbers may be used alone or in combination of two or more.
[0053] The butadiene-based rubber preferably has a sustainability rate of 30% by mass or more, more preferably 40% by mass or more, more preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 100% by mass. In order to make the sustainability rate of the butadiene-based rubber fall within the above range, for example, a polymer synthesized using butadiene derived from biological resources, butadiene derived from renewable resources, aromatic vinyl compounds derived from biological resources (e.g., styrene derived from biological resources), and aromatic vinyl compounds derived from renewable resources (e.g., styrene derived from renewable resources) as monomer components may be used. In this case, the synthesized polymer may be a homopolymer of a monomer derived from biological resources, a homopolymer of a monomer derived from renewable resources, a copolymer of a monomer derived from biological resources and a monomer derived from renewable resources, or a copolymer of a monomer derived from biological resources and / or a monomer derived from renewable resources and a monomer derived from a fossil resource (petroleum, etc.). In addition, the butadiene rubber (B-BR) derived from biological resources (biomass resources) and aromatic vinyl compound-butadiene copolymer rubber derived from biological resources (e.g., styrene-butadiene rubber (B-SBR) derived from biological resources (biomass resources)) include not only rubber obtained by polymerizing butadiene, etc. according to a conventional method, but also rubber obtained by reactions or enzyme reactions caused by microorganisms, plants, animals, and tissue cultures thereof (hereinafter also referred to as "microorganisms, etc.").
[0054] In order to set the sustainability rate of the entire other rubber components within the above range, it is preferable to use natural rubber (NR) as the other rubber components, or to use a polymer synthesized using monomer components derived from biological resources or monomer components derived from recycled resources as monomer components.
[0055] Generally, materials for rubber compositions for tires (rubber and its monomers, fillers, resins, etc.) require large-scale manufacturing equipment for their production, and are therefore usually produced in large factories in specific regions, and a lot of energy is required for the storage and transportation of raw materials and products. In contrast, materials derived from biological resources (biomass resources) are derived from agricultural products, forests, etc. in each region, and can be produced on a small scale by fermentation of microorganisms and catalytic reactions, so by utilizing products and waste from each region, the energy required for the transportation and storage of raw materials can be reduced, and further the energy required for the transportation and storage of the produced materials to tire factories can also be reduced, which is environmentally friendly. In addition, materials derived from regenerated resources (recycled resources) can be obtained, for example, by dismantling and pyrolyzing used tires to extract materials that constitute tires, such as rubber, fillers, and steel cords. In addition, sulfur can be obtained from biological resources or processed products of biological resources by a method including a desulfurization step of desulfurizing biological resources or processed products of biological resources to remove sulfur-containing substances from the biological resources or processed products of biological resources, a recovery step of recovering sulfur from the desulfurization residue generated in the desulfurization step, and a processing step of processing the recovered sulfur into sulfur for vulcanization (for example, the method described in Japanese Patent Application No. 2022-140390), and materials for rubber compositions for tires can be obtained from various wastes and used items. In this way, by using sustainable materials (materials derived from biological resources or materials derived from recycled resources), it is possible to reduce the overall environmental load in tire manufacturing, such as reducing carbon dioxide emissions (LCCO2) over the entire life cycle, reducing energy consumption (LCE) over the entire life cycle, reducing costs (LCC) incurred over the entire life cycle, and reducing the amount of fossil resources used.
[0056] In addition, when producing the rubber composition, the ratio of the monomer components derived from biological resources, the monomer components derived from renewable resources, and the monomer components derived from fossil resources can be appropriately selected according to the supply situation of biological resources, recycled resources, and fossil resources (e.g., monomer components derived from fossil resources) and / or market demand (e.g., demand for biological resources as food), and the monomer components derived from biological resources, the monomer components derived from renewable resources, and the monomer components derived from fossil resources can be polymerized to obtain rubber derived from sustainable materials (materials derived from biological resources or materials derived from renewable resources) having performance equivalent to that of conventional synthetic rubber. When using monomer components derived from renewable resources, it may be difficult to separate them from monomer components derived from fossil resources due to the manufacturing process of the monomer. In that case, the impact on the environment can be evaluated by adopting the concept of mass balance.
[0057] The ratio of each monomer unit (e.g., unit derived from isoprene, unit derived from butadiene, unit derived from aromatic vinyl compound) in the entire rubber component can be adjusted appropriately. The ratio of each monomer unit in the entire rubber component can be adjusted, for example, by appropriately combining the above-mentioned isoprene-based rubber and butadiene-based rubber. In addition, the ratio of cis-bond units in the unit derived from butadiene can also be adjusted appropriately. In this specification, the term "monomer unit" refers to a structural unit of a polymer, the term "unit derived from isoprene" refers to a structural unit in a polymer constituted based on the monomer isoprene (including the isoprene unit in natural rubber), the term "unit derived from butadiene" refers to a structural unit in a polymer constituted based on the monomer butadiene, and the term "unit derived from an aromatic vinyl compound" refers to a structural unit in a polymer constituted based on the monomer aromatic vinyl compound. In this specification, the ratio of each monomer unit is measured by NMR.
[0058] The other rubber components may include diene rubbers such as acrylonitrile-butadiene rubber (NBR), chloroprene rubber (CR), butyl rubber (IIR), styrene-isoprene-butadiene copolymer rubber (SIBR), etc., in addition to the above-mentioned isoprene-based rubber, butadiene rubber (BR), and aromatic vinyl compound-butadiene copolymer rubber (e.g., SBR). These rubber components may be used alone or in combination of two or more.
[0059] The other rubber components may be modified to introduce functional groups that interact with fillers such as carbon black and silica. Examples of the functional groups include amino groups, amide groups, isocyanate groups, imino groups, imidazole groups, urea groups, ammonium groups, imide groups, hydrazo groups, azo groups, diazo groups, carboxyl groups, nitrile groups, pyridyl groups, alkoxy groups, hydroxyl groups, oxy groups, epoxy groups, ether groups, carbonyl groups, oxycarbonyl groups, silyl groups, alkoxysilyl groups, mercapto groups, sulfide groups, disulfide groups, sulfonyl groups, sulfinyl groups, and thiocarbonyl groups. These functional groups may have a substituent. These functional groups may be introduced into the rubber component alone or in combination of two or more. Among these, an amino group, an alkoxy group, and an alkoxysilyl group are preferred, and a substituted amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, and an alkoxysilyl group having 1 to 6 carbon atoms are more preferred.
[0060] The functional group can be introduced, for example, by reacting a compound (modifier) having the functional group with the rubber component. The functional group is a modified functional group having an interactive property with a filler such as silica or carbon black, and examples thereof include a nitrogen-containing functional group, a silicon-containing functional group, and an oxygen-containing functional group. Examples of compounds (modifiers) having a nitrogen-containing functional group include amino group-containing compounds, and examples of compounds (modifiers) having a silicon-containing functional group include silicon halides and hydrocarbyloxysilane compounds. Examples of compounds (modifiers) having an oxygen-containing functional group include alkoxy group-containing compounds, alkylene oxide group-containing compounds, and trialkylsilyloxy group-containing compounds. More specifically, examples of the compounds include those described in International Publication No. 2016 / 194316 and International Publication No. 2019 / 117256. These modifiers may be used alone or in combination of two or more.
[0061] The rubber derived from sustainable materials (materials derived from biological resources or materials derived from renewable resources) can be produced in the same manner as conventional synthetic rubber derived from fossil resources, for example, by using monomer components derived from biological resources or monomer components derived from renewable resources, and, if necessary, monomer components derived from fossil resources. The rubber derived from sustainable materials (particularly rubber derived from biological resources) can also be obtained by reactions with microorganisms or enzyme reactions.
[0062] Regarding the method for preparing rubber derived from biological resources from the above-mentioned biological resources, for example, the method described in JP 2022-179158 A can be used. For example, by using butadiene obtained from biological resources as a monomer component, it is possible to obtain butadiene rubber (B-BR) derived from biological resources (biomass resources), and by using styrene obtained from biological resources and butadiene obtained from biological resources as monomer components, it is possible to obtain styrene-butadiene rubber (B-SBR) derived from biological resources (biomass resources). Here, methods for obtaining B-BR and B-SBR from biological resources include, in addition to artificial polymerization methods, methods of polymerization in vivo, and methods of polymerization with biological enzymes. The molecular weight, branching, microstructure, etc. of the obtained B-BR and B-SBR can be appropriately adjusted by changing the polymerization conditions according to known methods according to the target tire performance.
[0063] As the butadiene obtained from the biological resources, butadiene derived from alkyl alcohols (preferably ethanol and butanol, more preferably butanol), butadiene derived from alkenes (preferably ethylene), and butadiene derived from unsaturated carboxylic acids (preferably tiglic acid) can be suitably used. Two or more of these butadienes may be used in combination. As the styrene obtained from the biological resources, styrene obtained from a plant (preferably a plant belonging to the family Hamamelidaceae, Styraxaceae, or Apocynaceae, more preferably a plant belonging to the genera Liquidambar, Styrax, or Catharanthus, and even more preferably Sweetgum, Styrax rosa, or Catharanthus roseus) or a microorganism (preferably a microorganism belonging to the genera Penicillium or Escherichia, more preferably P. citrinum or transformed E. coli) can be suitably used. Two or more of these styrenes may be used in combination.
[0064] Recently, biomass combinat mainly using bioethanol, bioethylene, etc. are planned, but bioethanol and bioethylene are mainly produced using sugars and / or cellulose as biological resources, and other biological resources such as proteins, lipids, and amino acids cannot be effectively utilized. Furthermore, sugars compete with food, and excessive use of cellulose leads to deforestation. Therefore, it is preferable to use multiple types of monomer components derived from biological resources as the monomer components derived from the biological resources, or to use monomer components derived from biological resources, monomer components derived from renewable resources, and monomer components derived from fossil resources in combination, and further to appropriately adjust the ratio of these monomer components. This makes it possible to effectively utilize a wide range of biological resources and renewable resources such as sugars, proteins, and lipids without relying on one type of biological resource, and to stably supply rubber derived from sustainable materials, and further to consider the environment depending on the situation at the time of production. In addition, when using multiple types of monomer components derived from biological resources, it is preferable to use monomer components derived from different biological resources, i.e., monomer components obtained from different biological resources. Specifically, it is preferable to use a mixture of butadiene derived from multiple types of biological resources with different origins as the butadiene derived from biological resources, and / or to use a mixture of styrene derived from multiple types of biological resources with different origins as the styrene derived from biological resources. This allows multiple types of biological resources to be effectively utilized.
[0065] (resin) The rubber composition preferably further contains a resin. By containing the resin, the processability of the rubber composition can be improved and the wet performance when applied to a tire can be further improved. Examples of the resin include terpene resin, rosin resin, C5 resin, C5-C9 resin, C9 resin, cyclopentadiene resin, aromatic resin, coumarone resin, indene resin, coumarone-indene resin, olefin resin, polyurethane resin, acrylic resin, etc. These resins may be used alone or in combination of two or more. Among these resins, terpene resin, rosin resin, C5 resin, C5-C9 resin, C9 resin, cyclopentadiene resin, and aromatic resin are preferred, and terpene resin and rosin resin are particularly preferred. Terpene resin and rosin resin are naturally derived sustainable resins, so that they can further reduce the environmental load and can further improve tire performance, such as grip performance on various road surface conditions such as dry road surface, wet road surface, snowy road surface, and frozen road surface. In addition, C5 resin, C9 resin, C5-C9 resin, and cyclopentadiene resin can improve wear resistance and fuel economy in a well-balanced manner, while aromatic resin can improve grip performance, wear resistance, and rubber strength in a well-balanced manner.
[0066] The resin may be hydrogenated, i.e., may be a hydrogenated resin (hydrogenated resin). In addition, the resin may be modified to introduce a functional group that interacts with a filler such as carbon black or silica. Examples of the functional group include an amino group, an amide group, an isocyanate group, an imino group, an imidazole group, a urea group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, an epoxy group, an ether group, a carbonyl group, an oxycarbonyl group, a silyl group, an alkoxysilyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, and a thiocarbonyl group.
[0067] The terpene resin is a solid resin obtained by blending turpentine obtained at the same time when rosin is obtained from pine trees, or a polymerization component separated from the turpentine, and polymerizing the blend using a Friedel-Crafts catalyst, and examples of the terpene resin include β-pinene resin and α-pinene resin. The terpene resin also includes terpene-aromatic compound resin, and representative examples of the terpene-aromatic compound resin include terpene-phenol resin and styrene-terpene resin. The terpene-phenol resin can be obtained by reacting terpenes with various phenols using a Friedel-Crafts catalyst, or by further condensing the terpene with formalin. The styrene-terpene resin can be obtained by reacting styrene with terpenes using a Friedel-Crafts catalyst. The terpenes as the raw material are not particularly limited, and are preferably monoterpene hydrocarbons such as α-pinene and limonene, more preferably those containing α-pinene, and particularly preferably α-pinene.
[0068] Examples of the rosin-based resin include natural resin rosins such as gum rosin, tall oil rosin, and wood rosin contained in raw pine resin and tall oil. Examples of modified rosin, rosin derivatives, and modified rosin derivatives include polymerized rosin, partially hydrogenated rosin thereof, glycerin ester rosin, partially hydrogenated rosin thereof, and fully hydrogenated rosin thereof, pentaerythritol ester rosin, partially hydrogenated rosin thereof, and polymerized rosin, etc.
[0069] The C5 resins include aliphatic petroleum resins obtained by (co)polymerizing C5 fractions obtained by thermal cracking of naphtha in the petrochemical industry. C5 fractions usually include olefinic hydrocarbons such as 1-pentene, 2-pentene, 2-methyl-1-butene, 2-methyl-2-butene, and 3-methyl-1-butene, and diolefinic hydrocarbons such as 2-methyl-1,3-butadiene, 1,2-pentadiene, 1,3-pentadiene, and 3-methyl-1,2-butadiene.
[0070] The C5-C9 resin refers to a C5-C9 synthetic petroleum resin. Examples of the C5-C9 resin include petroleum-derived C5-C11 Examples of the solid polymers include those obtained by polymerizing the fraction using a Friedel-Crafts catalyst such as AlCl3 or BF3, and more specifically, copolymers mainly composed of styrene, vinyltoluene, α-methylstyrene, indene, etc. As the C5-C9 resin, a resin with a small amount of C9 or more components is preferred from the viewpoint of compatibility with the rubber component. Here, "a small amount of C9 or more components" means that the amount of C9 or more components in the total amount of the resin is less than 50 mass%, preferably 40 mass% or less.
[0071] The C9 resin refers to a C9 synthetic petroleum resin, for example, a solid polymer obtained by polymerizing a C9 fraction using a Friedel-Crafts catalyst such as AlCl3 or BF3. Examples of the C9 resin include copolymers mainly composed of indene, α-methylstyrene, vinyltoluene, etc.
[0072] The cyclopentadiene resin refers to a resin containing a unit derived from a cyclopentadiene monomer as a monomer unit. Examples of the cyclopentadiene resin include a homopolymer of a cyclopentadiene monomer, a copolymer of two or more cyclopentadiene monomers, and a copolymer of a cyclopentadiene monomer and another monomer. Here, examples of the cyclopentadiene monomer include cyclopentadiene, dicyclopentadiene, and tricyclopentadiene, and among these, dicyclopentadiene is preferred, that is, the cyclopentadiene resin is preferably a dicyclopentadiene resin. The dicyclopentadiene resin refers to a resin obtained by polymerizing dicyclopentadiene using a Friedel-Crafts catalyst such as AlCl3 or BF3. Examples of dicyclopentadiene resins include homopolymers of dicyclopentadiene, copolymers of dicyclopentadiene and aromatic monomers, and copolymers of dicyclopentadiene and C9 fractions (vinyl toluene, indene, etc.).
[0073] The aromatic resin refers to a resin containing a unit derived from an aromatic monomer as a monomer unit. Examples of the aromatic resin include a homopolymer of an aromatic monomer, a copolymer of two or more aromatic monomers, and a copolymer of an aromatic monomer and another monomer. Examples of the aromatic monomer include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-methoxystyrene, p-tert-butylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, and p-phenylstyrene; phenolic monomers such as phenol, alkylphenol, and alkoxyphenol; and naphthol monomers such as naphthol, alkylnaphthol, and alkoxynaphthol.
[0074] The softening point of the resin is preferably 30° C. or higher, more preferably 60° C. or higher, more preferably 80° C. or higher, more preferably higher than 110° C., more preferably 116° C. or higher, more preferably 120° C. or higher, more preferably 123° C. or higher, and even more preferably 127° C. or higher. From the viewpoint of processability, the softening point of the resin is preferably 160° C. or lower, more preferably 150° C. or lower, more preferably 145° C. or lower, more preferably 141° C. or lower, and even more preferably 136° C. or lower. In this specification, the softening point of the resin is the temperature at which the ball drops when the softening point defined in JIS K 6220-1:2015 (ISO 28641:2010) is measured using a ring and ball softening point tester.
[0075] As the resin, commercially available products can be used, and examples of commercially available resin products that can be used include products from ENEOS Corporation, Arakawa Chemical Industries, Ltd., ExxonMobil Corporation, Clayton Corporation, Yasuhara Chemical Co., Ltd., Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., Taoka Chemical Co., Ltd., and the like.
[0076] The content of the resin in the rubber composition is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the composition is applied, tire components, target performance, etc. For example, the content of the resin is preferably in the range of 5 to 100 parts by mass, and more preferably in the range of 10 to 60 parts by mass, per 100 parts by mass of the rubber component.
[0077] (Reinforcing filler) The rubber composition preferably further contains a reinforcing filler. This is because the vulcanized rubber composition of the present invention can have improved properties such as strength, abrasion resistance, low heat build-up, and wet performance. The reinforcing filler may be any reinforcing filler commonly used in the rubber field, such as carbon black, silica, talc, clay, aluminum hydroxide, and titanium oxide.
[0078] Examples of the silica include wet silica (hydrated silicic acid), dry silica (anhydrous silicic acid), calcium silicate, and aluminum silicate. Among these, wet silica is preferred because it has a large number of silanol groups. These silicas may be used alone or in combination of two or more. Commercially available products of the silica can be used, and examples of the commercially available silica products include products from Tosoh Silica Co., Ltd., Degussa, Rhodia, Solvay Japan Co., Ltd., Tokuyama Corporation, and the like.
[0079] As the silica, silica derived from silicic acid plants is preferred from the viewpoint of reducing environmental load. The silicic acid plants are present, for example, in mosses, ferns, horsetails, Cucurbitaceae, Urticaceae, and Gramineae plants. Among these plants, Gramineae plants are preferred. In addition, the Gramineae plants include rice, bamboo grass, sugarcane, and the like, among which rice is preferred. Since rice is widely cultivated for food, it can be procured locally in a wide area, and since rice husks are generated in large quantities as industrial waste, it is easy to secure the amount. Therefore, from the viewpoint of easy availability, silica derived from rice husks (hereinafter also referred to as "rice husk silica") is particularly preferred as silica. By using the rice husk silica, rice husks that become industrial waste can be effectively utilized, and since the raw material can be procured locally near the tire manufacturing plant, the energy and cost of transportation and storage can be reduced, which is environmentally preferable from various viewpoints. The rice husk silica may be a powder of rice husk charcoal obtained by carbonizing rice husks by heating, or may be precipitated silica produced by a wet method using an alkali silicate aqueous solution, which is prepared by extracting rice husk ash generated when rice husks are burned as fuel in a biomass boiler with an alkali and extracting the rice husk ash with an alkali silicate aqueous solution. The method for producing the rice husk charcoal is not particularly limited, and various known methods can be used. For example, rice husks can be pyrolyzed by steaming them in a kiln to obtain rice husk charcoal. The rice husk charcoal thus obtained is pulverized using a known pulverizer (for example, a ball mill), and then sorted and classified into a predetermined particle size range to obtain rice husk charcoal powder. The rice husk-derived precipitated silica can be produced by the method described in JP 2019-38728 A.
[0080] The silica has a nitrogen adsorption specific surface area (N2SA) of 50 m 2 / g or more, and 2 / g or more is more preferable, and 150m 2 / g or more is more preferable, and 350m 2 / g or less, and 2 / g or less is more preferable, 2 / g or less is more preferable, 2It is even more preferable that the molecular weight is not more than 1 / g. In this specification, the nitrogen adsorption specific surface area (N2SA) of silica is a value measured by the BET method in accordance with ASTM D3037-93.
[0081] The content of the silica can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, the tire components, the target performance, etc. For example, the content of the silica is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, more preferably 30 parts by mass or more, more preferably 50 parts by mass or more, more preferably 70 parts by mass or more, even more preferably 80 parts by mass or more, still more preferably 100 parts by mass or more, particularly preferably 110 parts by mass or more, and is preferably 300 parts by mass or less, more preferably 200 parts by mass or less, even more preferably 180 parts by mass or less, and particularly preferably 150 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0082] As the carbon black, carbon black derived from plants and carbon black obtained by recycling are particularly preferred. Examples of carbon black derived from plants include those derived from castor oil and rosin oil. Examples of carbon black obtained by recycling include carbon black obtained by pyrolysis of used tires and carbon black obtained from waste oil. The grade of the carbon black is not particularly limited, and examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. As the carbon black, commercially available products can be used, and examples of the commercially available carbon black include products from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shin-Nichika Carbon Co., Ltd., Columbia Carbon Co., Ltd., and the like. These carbon blacks may be used alone or in combination of two or more.
[0083] As the carbon black, carbon black derived from plants and carbon black obtained by recycling are particularly preferred. Examples of carbon black derived from plants include those derived from castor oil and rosin oil. Examples of carbon black obtained by recycling include carbon black obtained by pyrolysis of used tires and carbon black obtained from waste oil. The grade of the carbon black is not particularly limited, and examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. As the carbon black, commercially available products can be used, and examples of the commercially available carbon black include products from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shinnikka Carbon Co., Ltd., Columbia Carbon Co., Ltd., and the like. These carbon blacks may be used alone or in combination of two or more.
[0084] The content of the carbon black is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber is applied, the tire components, the target performance, etc. For example, the content of the carbon black is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component.
[0085] The proportion of silica in the total content of silica and carbon black is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category, tire components, target performance, etc. of the tire to which it is applied. For example, in the case of tread rubber for passenger car tires, the proportion of silica in the total content of silica and carbon black is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. In addition, the proportion of silica in the total content of silica and carbon black may be 100% by mass, but is preferably 98% by mass or less.
[0086] (Silane coupling agent) In addition, when the rubber composition contains silica, it is preferable that the rubber composition contains a silane coupling agent in order to improve the effect of the silica. Examples of the silane coupling agent include bis(3-triethoxysilylpropyl)tetrasulfide, bis(3-triethoxysilylpropyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyltetrasulfide, 3-triethoxysilylpropyl-N, Examples of the silane coupling agent include N-dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, 3-trimethoxysilylpropyl benzothiazolyl tetrasulfide, 3-triethoxysilylpropyl benzothiazolyl tetrasulfide, 3-triethoxysilylpropyl methacrylate monosulfide, 3-trimethoxysilylpropyl methacrylate monosulfide, bis(3-diethoxymethylsilylpropyl)tetrasulfide, 3-mercaptopropyldimethoxymethylsilane, dimethoxymethylsilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, dimethoxymethylsilylpropyl benzothiazolyl tetrasulfide, etc. As the silane coupling agent, a commercially available product can be used, and examples of the commercially available silane coupling agent include products from Degussa, Momentive, Shin-Etsu Silicone Co., Ltd., Dow Corning Toray Co., Ltd., Tokyo Chemical Industry Co., Ltd., and Azumax Co., Ltd. These silane coupling agents may be used alone or in combination of two or more.
[0087] The content of the silane coupling agent can be appropriately adjusted depending on, for example, the tire category to which it is applied, the tire components, the target performance, etc. For example, the content of the silane coupling agent is preferably 1 part by mass or more, more preferably 6 parts by mass or more, and even more preferably 8 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, even more preferably 12 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the silica.
[0088] (rubber powder) The rubber composition preferably contains rubber powder. The rubber powder may be obtained by crushing used rubber products such as used tires, removing reinforcing materials such as steel materials and fibers, dust, glass, sand, stones, etc., as desired, or preparing a new vulcanized rubber composition for producing rubber powder and crushing the rubber powder. For example, rubber powder can be obtained from vulcanized rubber by the method described in "Rubber Chemistry And Technology". In the process of crushing vulcanized rubber to obtain rubber powder, mechanical treatment or low-temperature treatment may be used. For example, in the mechanical treatment, various crushing devices such as a cracker mill and a granulator can be used to mechanically crush the vulcanized rubber into fine particles. In the low-temperature treatment, the finely chopped vulcanized rubber is frozen at a very low temperature and then crushed into fine particles. In addition, a magnetic separator or the like can be used to remove steel materials, and an air separator or the like can be used to remove fibers. As the rubber powder, a commercially available product can be used, and examples of the commercially available rubber powder include products from Global Corporation or Nantong Huili Rubber Corporation. From the viewpoint of reducing the environmental load, it is preferable to use rubber powder obtained by crushing used rubber products such as used tires. The rubber powder may be used alone or in combination of two or more kinds.
[0089] The composition of the rubber powder is not particularly limited, and depends on the composition of vulcanized rubber such as used rubber products (used tires) that serve as a raw material. In one embodiment, the rubber powder contains a rubber component, carbon black, silica, etc. The rubber component, carbon black, silica, etc. contained in the rubber powder may be the same as or different from the rubber component, carbon black, silica, etc. contained in the rubber composition of the present embodiment described above.
[0090] The rubber powder has a volume average particle size of preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 200 μm or less, and even more preferably 100 μm or less. The smaller the volume average particle size of the rubber powder, the better, and there is no particular lower limit. In this specification, the volume average particle size is measured by a laser diffraction particle size distribution measuring device, for example, "CAPA500" manufactured by Horiba, Ltd.
[0091] The rubber powder has a 60 mesh sieve residue of preferably less than 1 mass%, more preferably 0.5 mass% or less, and even more preferably 0.1 mass% or less, with no particular lower limit. Also, the rubber powder has an 80 mesh sieve residue of preferably less than 10 mass%, more preferably 1 mass% or less, and even more preferably 0.5 mass% or less, with no particular lower limit. In this specification, the sieve residue is measured in accordance with ASTM D5644-01.
[0092] The rubber powder has an acetone extractable content of preferably 12% by mass or less, more preferably 11% by mass or less, and even more preferably 10% by mass or less, and preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more. In this specification, the acetone extractables in the rubber crumb means the acetone extractables (%) determined by the acetone extraction method in accordance with JIS K6350.
[0093] The content of rubber powder in the rubber component is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber component is applied, tire components, target performance, etc. For example, the content of rubber powder is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, and is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, more preferably 100 parts by mass or less, more preferably 50 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, and particularly preferably 5 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0094] (liquid softener) Furthermore, the rubber composition may contain a liquid softener. Here, the "liquid softener" is a compounding agent that is liquid at 25°C (room temperature) and has the effect of softening the rubber composition. The liquid softener is not particularly limited, and examples thereof include oil and liquid polymer, among which oil is preferable. These liquid softeners may be used alone or in combination of two or more.
[0095] The oil is a general term for the extender oil contained in the rubber component and the liquid oil added as a compounding agent of the rubber composition, and examples thereof include vegetable oil, process oil, oil obtained by recycling vegetable oil or process oil, or a mixture thereof. From the viewpoint of reducing the environmental load, the oil is preferably vegetable oil or oil obtained by recycling. Examples of the vegetable oil include palm oil, castor oil, cottonseed oil, soybean oil, linseed oil, rapeseed oil, coconut oil, peanut oil, pine oil, pine tar, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive oil, sunflower oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, tung oil, coconut oil, etc. Examples of the process oil include paraffin-based process oil, aromatic process oil, naphthene-based process oil, etc. The oil may be a commercially available product, and examples of the commercially available oil include products from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., Japan Energy Co., Ltd., Orisoi Co., Ltd., H&R Corporation, Toyokuni Oil Mills Co., Ltd., Showa Shell Sekiyu K.K., Nisshin Oillio Group Co., Ltd., Fuji Kosan Co., Ltd., etc. These oils may be used alone or in combination of two or more.
[0096] The liquid polymer is preferably a liquid diene polymer. Examples of the liquid diene polymer include liquid styrene-butadiene copolymer (liquid SBR), liquid polybutadiene (liquid BR), liquid polyisoprene (liquid IR), liquid styrene-isoprene copolymer (liquid SIR), liquid styrene-butadiene-styrene block copolymer (liquid SBS block polymer), liquid styrene-isoprene-styrene block copolymer (liquid SIS block polymer), liquid polyfarnesene, and liquid farnesene-butadiene copolymer. These liquid polymers may be hydrogenated, or the terminals or main chains may be modified with functional groups (polar groups). These liquid polymers may be used alone or in combination of two or more.
[0097] The content of the liquid softener is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which it is applied, the tire components, the target performance, etc. For example, the content of the liquid softener is preferably 5 parts by mass or more, and more preferably 10 parts by mass or more, and is preferably 100 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 50 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0098] (Anti-aging agent) Furthermore, the rubber composition may contain an antioxidant, such as N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD), N,N'-bis(1,4-dimethylpentyl)-p-phenylenediamine (77PD), N,N'-diphenyl-p-phenylenediamine (DPPD), N,N'-bis(1-ethyl-3-methylpentyl)-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline polymer (TMDQ), 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline (AW), and 6-anilino-2,2,4-trimethyl-1,2-dihydroquinoline. As the antiaging agent, commercially available products can be used, and examples of the commercially available antiaging agent include products from Ouchi Shinko Chemical Industry Co., Ltd., Sumitomo Chemical Co., Ltd., Seiko Chemical Co., Ltd., Flexis Co., Ltd., etc. These antiaging agents may be used alone or in combination of two or more.
[0099] The content of the antiaging agent is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which it is applied, the tire components, the target performance, etc. For example, the content of the antiaging agent is preferably 1 part by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2 parts by mass or more, and is preferably 12 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 8 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0100] (wax) The rubber composition may contain a wax. Examples of the wax include natural waxes such as vegetable wax and animal wax; petroleum waxes such as paraffin wax and microcrystalline wax; and synthetic waxes such as ethylene polymers and propylene polymers. Commercially available waxes can be used, and examples of the commercially available waxes include products from Seiko Chemical Co., Ltd., Nippon Seiro Co., Ltd., Ouchi Shinko Chemical Co., Ltd., and the like. These waxes may be used alone or in combination of two or more.
[0101] The content of the wax is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber is applied, the tire components, the target performance, etc. For example, the content of the wax is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and is preferably 10 parts by mass or less, more preferably 6 parts by mass or less, based on 100 parts by mass of the rubber component.
[0102] (Stearic acid) The rubber composition may contain stearic acid. Commercially available stearic acid may be used, and examples of the commercially available stearic acid include products from NOF Corp., Kao Corp., Fujifilm Wako Pure Chemical Corp., Chiba Fatty Acid Corp., etc. These commercially available stearic acid products may be used alone or in combination of two or more.
[0103] The content of the stearic acid is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, the tire components, the target performance, etc. For example, the content of the stearic acid is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 6 parts by mass or less, per 100 parts by mass of the rubber component.
[0104] (Zinc Oxide) The rubber composition may also contain zinc oxide (zinc white). The zinc oxide is preferably zinc oxide obtained by recycling. Commercially available products can be used as the zinc oxide, and examples of the commercially available zinc oxide include products from Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., and the like. These commercially available zinc oxide products may be used alone or in combination of two or more.
[0105] The content of the zinc oxide is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, the tire components, the target performance, etc. For example, the content of the zinc oxide is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 6 parts by mass or less, per 100 parts by mass of the rubber component.
[0106] (sulfur) Furthermore, the rubber composition preferably contains sulfur. The sulfur may be derived from fossil resources, recycled resources, or materials derived from biological resources. From the viewpoint of reducing the environmental load, it is particularly preferable to use sulfur obtained from waste derived from biological resources. Examples of a method for obtaining sulfur from waste derived from biological resources include the method described in the above-mentioned Japanese Patent Application No. 2022-140390. In addition, the sulfur may be powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are generally used as crosslinking agents in the rubber industry. As the sulfur, commercially available products can be used, and examples of commercially available sulfur products include products from Tsurumi Chemical Industry Co., Ltd., Hosoi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Co., Ltd., Nippon Kanzuri Kogyo Co., Ltd., etc. These sulfurs may be used alone or in combination of two or more types.
[0107] The sulfur content is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber is applied, tire components, target performance, etc. For example, the sulfur content is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.8 parts by mass or more, and is preferably 8 parts by mass or less, and more preferably 5 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0108] (void-introducing agent) The rubber composition preferably further contains a void-introducing agent. By containing the void-introducing agent in the rubber composition, the vulcanized rubber has voids on the surface or inside, or on the surface and inside, so that a tire using the vulcanized rubber has flexibility and is easily in contact with an icy road surface, and water on the road surface is absorbed into the voids on the tire surface, and water is easily removed from the road surface, so that the braking performance on wet or frozen road surfaces can be improved.
[0109] Examples of the void-introducing agent include foaming agents, metal sulfates, thermally expandable microcapsules, porous cellulose particles, lignin derivatives, etc., and one of these may be used alone or two or more may be mixed together. Furthermore, from the viewpoint of performance on ice, it is preferable to use the foaming agents.
[0110] The content of the void-introducing agent in the rubber composition is not particularly limited, but from the viewpoint of obtaining a desired void ratio and maintaining abrasion resistance, etc., the content is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass, and even more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the rubber component.
[0111] Foaming agent By containing a foaming agent as the void-introducing agent in the rubber composition, air bubbles are generated in the vulcanized rubber by the foaming agent during vulcanization of the rubber composition, and the vulcanized rubber can be made into foamed rubber. Since the foamed rubber has flexibility, the tire surface using the vulcanized rubber can easily adhere to an icy road surface. In addition, the air bubbles generate holes (foam holes) originating from the air bubbles in the vulcanized rubber surface and the tire surface, which function as water channels for draining water. Specific examples of the foaming agent include inorganic foaming agents such as azodicarbonamide (ADCA), dinitrosopentamethylenetetramine (DPT), dinitrosopentastyrenetetramine, benzenesulfonylhydrazide derivatives, p,p'-oxybisbenzenesulfonylhydrazide (OBSH), carbonates such as ammonium carbonate, sodium carbonate, and potassium carbonate, bicarbonates (hydrogen carbonates) such as ammonium bicarbonate, sodium bicarbonate, and potassium bicarbonate, nitrososulfonyl azo compounds that generate nitrogen, N,N'-dimethyl-N,N'-dinitrosophthalamide, toluenesulfonylhydrazide, p-toluenesulfonylsemicarbazide, and p,p'-oxybisbenzenesulfonylsemicarbazide. Among these, from the viewpoint of manufacturing processability, it is preferable to use azodicarbonamide (ADCA), dinitrosopentamethylenetetramine (DPT), and inorganic foaming agents, and it is more preferable to include at least sodium bicarbonate. These foaming agents may be used alone or in combination of two or more.
[0112] The content of the foaming agent in the rubber composition is not particularly limited, but is preferably 1 to 10 parts by mass, and more preferably 2 to 8 parts by mass, per 100 parts by mass of the rubber component. The rubber composition may further contain a foaming assistant such as urea, zinc stearate, zinc benzenesulfinate, zinc oxide, etc. These may be used alone or in combination of two or more. By using a foaming assistant in combination, the foaming reaction is promoted to increase the degree of completion of the reaction, and unnecessary deterioration over time can be suppressed.
[0113] Metal sulfates When the rubber composition contains a metal sulfate as the void-introducing agent, the metal sulfate protrudes from the tire surface obtained by vulcanizing the rubber composition and performs a claw function without the disadvantage of being abrasive. The metal sulfate then gradually leaves the rubber matrix, creating cavities that act as storage volumes and passages for the evacuation of the water film on the ice surface. Under these conditions, the contact between the tire surface (e.g., the surface of the tread) and the ice is no longer lubricated, and therefore, the metal sulfate that improves the coefficient of friction is, for example, magnesium sulfate.
[0114] The metal sulfate is preferably in the form of micrometer-sized particles, specifically, the average particle size and median particle size (both expressed by mass) are preferably from 1 μm to 1 mm, and the median particle size is more preferably from 2 μm to 800 μm. The average particle size and the median particle size are 1 μm or more, so that the desired technical effect (i.e., the formation of an appropriate micro-roughness) can be easily obtained. Also, the average particle size and the median particle size are 1 mm or less, so that the deterioration of aesthetics can be suppressed (the appearance of too obvious particles on the tread surface can be suppressed) and the grip performance on melting ice can be prevented from being impaired, particularly when the rubber composition is used as a tread.
[0115] For all these reasons, the median particle size of the metal sulfate is preferably between 2 μm and 500 μm, more preferably between 5 μm and 200 μm. This particularly preferred particle size range appears to correspond to an optimal compromise between the desired surface roughness on the one hand and good contact of the rubber composition with the road surface on the other hand. Furthermore, for the same reason as above, the content of the metal sulfate in the rubber composition is preferably 5 to 40 parts by mass, and more preferably 10 to 35 parts by mass, per 100 parts by mass of the rubber component.
[0116] In addition, various known methods for analyzing particle size and calculating the median particle size of microparticles (or the average diameter of microparticles assuming a substantially spherical shape), for example by laser diffraction, are applicable (see, for example, standard ISO-8130-13 or standard JIS K5600-9-3). Particle size analysis by mechanical sieving may also be used simply and preferably; the procedure consists in sieving a defined amount of sample (for example 200 g) for 30 minutes on a vibrating table through various sieve diameters (for example through meshes of 1000, 800, 630, 500, 400, ... 100, 80 and 63 μm, according to a progression ratio equal to 1.26); the oversizes collected on each sieve are weighed on a precision balance; the percentage of the oversizes at each mesh diameter relative to the total mass of the substance is estimated from the weighing; finally, the median particle size (or median diameter) or mean particle size (or mean diameter) is calculated in a known manner from a histogram of the particle size distribution.
[0117] Thermally expandable microcapsules The thermally expandable microcapsules have a structure in which a thermally expandable substance is encapsulated in a shell material formed of a thermoplastic resin. The shell material of the thermally expandable microcapsules can be formed of a nitrile polymer. The thermally expandable substance contained in the shell material of the microcapsule has a property of vaporizing or expanding by heat, and is exemplified by at least one selected from the group consisting of hydrocarbons such as isoalkanes and normal alkanes. Examples of isoalkanes include isobutane, isopentane, 2-methylpentane, 2-methylhexane, and 2,2,4-trimethylpentane, and examples of normal alkanes include n-butane, n-propane, n-hexane, n-heptane, and n-octane. These hydrocarbons may be used alone or in combination. A preferred form of the thermally expandable substance is one in which a hydrocarbon that is gaseous at room temperature is dissolved in a hydrocarbon that is liquid at room temperature. By using such a mixture of hydrocarbons, sufficient expansion force can be obtained from the low temperature region to the high temperature region in the vulcanization molding temperature range (150°C to 190°C) of an unvulcanized tire.
[0118] Examples of such thermally expandable microcapsules that can be used include those manufactured by Expancel of Sweden under the trade names "EXPANCEL 091DU-80" or "EXPANCEL 092DU-120," and those manufactured by Matsumoto Yushi Seiyaku Co., Ltd. under the trade names "Matsumoto Microsphere F-85D" or "Matsumoto Microsphere F-100D."
[0119] The content of the thermally expandable microcapsules in the rubber composition is preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the rubber component.
[0120] ·Porous cellulose particles When the rubber composition contains porous cellulose particles as the void-introducing agent, if the porous cellulose particles are exposed on the surface of a tire obtained by vulcanizing the rubber composition, water on the snowy and icy road surface is absorbed by the porous cellulose particles, and water can be removed between the tire and the road surface. In addition, the presence of cellulose, which is a polysaccharide, causes an interaction between the tire and water on the snowy and icy road surface, so that the interaction between the tire and water by the modified polyoxyalkylene glycol can be further enhanced.
[0121] The porous cellulose particles are cellulose particles having a porous structure with a porosity of 75 to 95%, and by blending them with a rubber composition, the performance on ice can be significantly improved. When the porosity of the porous cellulose particles is 75% or more, the effect of improving the performance on ice is excellent, and when the porosity is 95% or less, the strength of the particles can be increased. The porosity is more preferably 80 to 90%. The porosity of the porous cellulose particles can be calculated by measuring the volume of a given mass of a sample (that is, the porous cellulose particles) with a measuring cylinder, determining the bulk density, and then using the following formula. Porosity [%] = {1-(bulk specific gravity of sample [g / ml]) / (true specific gravity of sample [g / ml])} x 100 Here, the true specific gravity of cellulose is 1.5.
[0122] The particle size of the porous cellulose particles is not particularly limited, but from the viewpoint of abrasion resistance, the average particle size is preferably 1000 μm or less. The lower limit of the average particle size is not particularly limited, but it is preferably 5 μm or more. The average particle size is more preferably 100 to 800 μm, and further preferably 200 to 800 μm.
[0123] The porous cellulose particles are preferably spherical particles having a major axis / minor axis ratio of 1 to 2. By using particles having such a spherical structure, it is possible to improve dispersibility in the rubber composition, thereby contributing to improving performance on ice and maintaining abrasion resistance, etc. The major axis / minor axis ratio is more preferably 1.0 to 1.5.
[0124] The average particle size and major axis / minor axis ratio of porous cellulose particles are determined as follows: porous cellulose particles are observed under a microscope to obtain an image, and the major axis and minor axis of 100 particles are measured using this image (when the major axis and minor axis are the same, the length in a certain axis direction and the length in an axis direction perpendicular to the major axis) and the average value is calculated to obtain the average particle size, and the major axis / minor axis ratio is obtained by averaging the values obtained by dividing the major axis by the minor axis.
[0125] Such porous cellulose particles are commercially available from Rengo Co., Ltd. under the name "Viscopearl" and are also described in JP-A-2001-323095, JP-A-2004-115284, etc., and these can be suitably used. The content of the porous cellulose particles in the rubber composition is preferably 0.3 to 20 parts by mass per 100 parts by mass of the rubber component. By having a content of 0.3 parts by mass or more, it is possible to enhance the effect of improving performance on ice, and by having a content of 20 parts by mass or less, it is possible to prevent the rubber hardness from becoming too high, and to prevent a decrease in abrasion resistance. The content of the porous cellulose particles is more preferably 1 to 15 parts by mass, and further preferably 3 to 15 parts by mass.
[0126] Lignin derivatives When the rubber composition contains a lignin derivative as the void-introducing agent, the effect of improving performance on ice can be further enhanced. Here, lignin sulfonates are preferably used as the lignin derivative. Examples of lignin sulfonates include alkali metal salts, alkaline earth metal salts, ammonium salts, and alcoholamine salts of lignin sulfonic acid, and at least one of these can be used. Preferred are alkali metal salts and / or alkaline earth metal salts of lignin sulfonic acid, such as potassium salts, sodium salts, calcium salts, magnesium salts, lithium salts, and barium salts, and mixed salts thereof may also be used.
[0127] (foaming aid) Furthermore, when the rubber composition contains a foaming agent as the void-introducing agent, it is preferable that the rubber composition further contains a foaming assistant. Examples of the foaming assistant include urea, zinc stearate, zinc benzenesulfinate, zinc oxide, etc. These may be used alone or in combination of two or more. By using the foaming assistant in combination, it becomes possible to promote the foaming reaction, increase the degree of completion of the reaction, and suppress unnecessary deterioration over time.
[0128] Furthermore, the total content of the foaming agent and the foaming assistant is preferably 1 to 30 parts by mass relative to 100 parts by mass of the rubber component. When the total content of the foaming agent and the foaming assistant is 1 part by mass or more, the rubber composition can be sufficiently foamed during vulcanization, and the foaming rate of the vulcanized rubber can be maintained high. On the other hand, even when the total content of the foaming agent and the foaming assistant is 30 parts by mass or less, the decrease in the foaming rate can be suppressed. From the viewpoint of suppressing the decrease in the foaming rate as described above, the total content of the foaming agent and the foaming assistant is preferably 3 parts by mass or more, and more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component. Also, from the viewpoint of suppressing the decrease in the foaming rate as described above, the total content of the foaming agent and the foaming assistant is preferably 25 parts by mass or less, and more preferably 20 parts by mass or less, per 100 parts by mass of the rubber component.
[0129] In addition, in the rubber composition, the mass ratio of the foaming agent to the foaming aid (foaming agent:foaming aid) is preferably 1:1.1 to 1:3.3. If the mass ratio (foaming agent:foaming aid) is less than 1:1.1, the rubber composition may not foam sufficiently during vulcanization, and the foaming rate of the vulcanized rubber may decrease. On the other hand, if the mass ratio (foaming agent:foaming aid) exceeds 1:3.3, the foaming rate may also decrease. From the viewpoint of suppressing the decrease in the expansion rate as described above, the mass ratio of the foaming agent to the foaming assistant (foaming agent:foaming assistant) is preferably 1:1.2 or more, and more preferably 1:1.3 or more. Also, from the viewpoint of suppressing the decrease in the expansion rate as described above, the mass ratio of the foaming agent to the foaming assistant (foaming agent:foaming assistant) is preferably 1:3.2 or less, more preferably 1:3.1 or less, even more preferably 1:2.9 or less, even more preferably 1:2.7 or less, even more preferably 1:2.5 or less, and particularly preferably 1:2.3 or less.
[0130] From the viewpoint of the foaming rate of the vulcanized rubber and the wet performance of the tire, the content of the foaming aid is preferably in the range of 4 to 14 parts by mass, and more preferably in the range of 6 to 14 parts by mass, per 100 parts by mass of the rubber component.
[0131] (organic acid) The rubber composition may contain an organic acid as required. In this case, the SP value of the organic acid is 9.15 to 16.0 (cal / cm 3 ) 1 / 2It is preferable that the organic acid is a compound having an organic acid group. The organic acid has an effect of improving the foaming rate of the vulcanized rubber by balancing the rate of the decomposition and foaming reaction of the foaming agent and the rate of the vulcanization reaction of the rubber composition during vulcanization of the rubber composition. Therefore, by blending the organic acid with the rubber composition, the workability of the rubber composition is maintained good, while the decomposition and foaming reaction of the foaming agent is promoted, and the rate of the decomposition and foaming reaction and the rate of the vulcanization reaction of the rubber composition are balanced to improve the foaming rate of the vulcanized rubber, and by applying the rubber composition to a tire, the wet performance of the tire can be improved. The SP value of the organic acid is 9.15 (cal / cm 3 ) 1 / 2 If the SP value of the organic acid is less than 16.0 (cal / cm 3 ) 1 / 2 If it exceeds this range, the adhesiveness of the rubber composition containing the organic acid will be high, and the rubber composition may adhere to manufacturing equipment such as rolls during production of the rubber composition, which may deteriorate the workability of the rubber composition.
[0132] From the same viewpoint, the SP value of the organic acid is 10.5 to 14.3 (cal / cm 3 ) 1 / 2 It is preferable that the SP value of the organic acid is 10.5 (cal / cm 3 ) 1 / 2 When the SP value of the organic acid is 14.3 (cal / cm 3 ) 1 / 2 When the content is equal to or less than this, the adhesion of the rubber composition containing an organic acid can be further reduced, and the workability of the rubber composition can be further improved. The general-purpose stearic acid used as a vulcanization aid for the rubber composition has an SP value of 9.12 (cal / cm 3 ) 1 / 2 and the effect of promoting the decomposition of the foaming agent is low. In this specification, the SP value (solubility parameter) of an organic acid is calculated according to the Fedors method.
[0133] The organic acid may be any of monocarboxylic acids, dicarboxylic acids, tricarboxylic acids, etc., and may be aliphatic or aromatic. Furthermore, it may have a functional group other than a carboxyl group, such as a hydroxyl group, a ketone group, or an ethylenically unsaturated group. The organic acid is preferably an aromatic ring-containing (aromatic) acid, and more preferably a monocarboxylic acid. When the organic acid has an aromatic ring, the adhesion of the rubber composition can be further reduced, the workability of the rubber composition is further improved, and the rubber composition is further less likely to adhere to manufacturing equipment such as rolls.
[0134] Examples of the aliphatic monocarboxylic acid include palmitic acid. Examples of the aliphatic dicarboxylic acid include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. Examples of the aromatic monocarboxylic acid include benzoic acid and salicylic acid. Examples of the aromatic dicarboxylic acid include phthalic acid. Examples of organic acids having a functional group other than a carboxyl group include tartaric acid, malic acid, maleic acid, glycolic acid, and α-ketoglutaric acid. The organic acids may be used alone or in combination of two or more.
[0135] In addition, it is particularly preferable to use benzoic acid as the organic acid. When benzoic acid is blended into the rubber composition, the adhesion of the rubber composition can be further reduced, the workability of the rubber composition is further improved, and the rubber composition becomes less likely to adhere to manufacturing equipment such as rolls.
[0136] The content of the organic acid is preferably 0.1 to 7 parts by mass, more preferably 1.5 to 7 parts by mass, and even more preferably 3 to 7 parts by mass, per 100 parts by mass of the rubber component, from the viewpoints of workability of the rubber composition, foaming rate of the vulcanized rubber, and wet performance of the tire. From the viewpoint of the foaming rate of the vulcanized rubber and the wet performance of the tire, the total content of the foaming agent and the organic acid is preferably 3 parts by mass or more and less than 15 parts by mass, more preferably 5 parts by mass or more and less than 15 parts by mass, and even more preferably 7 parts by mass or more and less than 15 parts by mass, relative to 100 parts by mass of the rubber component. Furthermore, the mass ratio of the foaming agent to the organic acid (foaming agent:organic acid) is preferably in the range of 1:0.5 to 1:1.5, and more preferably in the range of 1:0.7 to 1:1.3, from the viewpoints of the foaming rate of the vulcanized rubber and the wet performance of the tire.
[0137] (Composite Fiber) The rubber composition preferably further contains composite fibers. By containing the above-mentioned composite fiber, affinity with water can be sufficiently ensured, and excellent drainage properties and wet performance can be imparted, particularly when used for tire applications. The composite fiber is preferably made of a hydrophilic resin having a coating layer formed on the surface thereof, because providing a coating layer on the surface of the composite fiber improves the dispersibility of the composite fiber in the rubber composition. In addition, the hydrophilic resin is preferably insoluble in water. By using a water-insoluble hydrophilic resin, dissolution of the composite fiber can be suppressed even when the composite fiber is exposed on the surface of a product (e.g., a tire).
[0138] The hydrophilic resin is not particularly limited as long as it is a resin that can exhibit affinity with water, that is, a resin that has a hydrophilic group in the molecule, but specifically, it is preferably a resin that contains an oxygen atom, a nitrogen atom, or a sulfur atom, and examples thereof include resins that contain at least one group selected from the group consisting of -OH, -C(=O)OH, -OC(=O)R (R is an alkyl group), -NH2, -NCO, and -SH. Among these groups, -OH, -C(=O)OH, -OC(=O)R, -NH2, and -NCO are preferred. More specifically, the hydrophilic resin may be an ethylene-vinyl alcohol copolymer, a vinyl alcohol homopolymer, a poly(meth)acrylic acid resin or an ester resin thereof (hereinafter, a copolymer containing a structural unit derived from (meth)acrylic acid and a (co)polymer containing a structural unit derived from a (meth)acrylic acid ester are collectively referred to as a (meth)acrylic resin), a polyamide resin, a polyethylene glycol resin, a carboxyvinyl copolymer, a styrene-maleic acid copolymer, a polyvinylpyrrolidone resin, a vinylpyrrolidone-vinyl acetate copolymer, a polyester resin, a cellulose-based resin, etc. Among these, an ethylene-vinyl alcohol copolymer, a vinyl alcohol homopolymer, a poly(meth)acrylic acid resin, a polyamide resin, an aliphatic polyamide-based resin, an aromatic polyamide-based resin, a polyester resin, a polyvinyl alcohol-based resin, a cellulose-based resin, or a (meth)acrylic resin is preferred, and an ethylene-vinyl alcohol copolymer is more preferred.
[0139] The surface of the fiber made of the hydrophilic resin is preferably coated with a coating layer made of a low-melting resin (hereinafter also referred to as "low-melting resin") having affinity for the rubber component and preferably having a melting point lower than the maximum vulcanization temperature. By forming such a coating layer, it is possible to effectively maintain the affinity of the hydrophilic resin itself with water while exhibiting good affinity with the rubber component near the composite fiber, and to capture the hydrophilic resin that is difficult to melt during vulcanization (foaming), and to promote the formation of cavities inside the composite fiber. That is, it is possible to ensure good dispersion of the composite fiber in the rubber component, fully exhibit the drainage effect due to the hydrophilic resin, and also to fully exhibit the wet performance improvement effect due to the voids present inside the composite fiber. In addition, the low-melting resin melts during vulcanization to become a fluid coating layer, which contributes to adhesion between the rubber component and the composite fiber, and imparts good wet performance and abrasion resistance. The thickness of the coating layer may vary depending on the amount of the hydrophilic resin and the average diameter of the composite fiber, but is preferably 0.001 to 10 μm, more preferably 0.001 to 5 μm. By forming the coating layer with a thickness within the above range, the desired effects of the present invention can be fully achieved. The coating layer may be formed over the entire surface of the hydrophilic resin, or may be formed on a part of the surface of the hydrophilic resin. Specifically, it is preferable that the coating layer is formed so as to occupy at least 50% of the total surface area of the hydrophilic resin.
[0140] Specifically, the low melting point resin used in the coating layer is preferably a resin in which the polar component is 50% by mass or less relative to the total components, and more preferably a polyolefin resin. If the polar component is within the above range relative to the total components, the resin has an appropriate difference in SP value with the rubber component, and has an appropriately lower melting point than the maximum vulcanization temperature, and can easily melt during vulcanization while sufficiently securing good affinity with the rubber component, thereby promoting foaming of the vulcanized rubber. Therefore, it is possible to reliably form cavities inside the composite fiber while more reliably improving the dispersibility of the fiber made of the hydrophilic resin in the rubber composition.
[0141] The polyolefin resin may be branched, linear, or the like. It may also be an ionomer resin in which ethylene-methacrylic acid copolymer molecules are crosslinked with metal ions. Specifically, the polyolefin resin may be polyethylene, polypropylene, polybutene, polystyrene, ethylene-propylene copolymer, ethylene-methacrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-propylene-diene terpolymer, ethylene-vinyl acetate copolymer, and ionomer resins thereof. These may be used alone or in combination of two or more. Among these, the polyolefin resin is preferably a polyethylene resin, a polypropylene resin, a polyolefin ionomer, or a maleic anhydride-modified α-polyolefin. When a polyolefin ionomer or a maleic anhydride-modified α-polyolefin is used, it also adheres to the hydroxyl group of the hydrophilic resin, so that the rubber strength can be further improved.
[0142] To manufacture a composite fiber made of a hydrophilic resin on which a coating layer made of the low melting point resin is formed, a method can be adopted in which these resins are blended using a mixing mill, melt spun to form an undrawn yarn, and the undrawn yarn is hot-drawn to form a fiber. Alternatively, a method can be adopted in which the resins are blended using two twin-screw extruders equipped with dies, and then similarly formed into a fiber. In this case, the hydrophilic resin and the low melting point resin are extruded simultaneously from the two die outlets, and the undrawn yarn is formed from this. The amount of these resins to be put into the mixing mill or hopper can vary depending on the length and diameter of the composite (fiber) to be obtained, but the amount of the low melting point resin is preferably 5 to 300 parts by mass, more preferably 10 to 150 parts by mass, per 100 parts by mass of the hydrophilic resin. By putting these resins in the amount within the above range, a coating layer capable of exerting the desired effect is effectively formed on the surface of the composite (fiber) made of the hydrophilic resin obtained after the drawing process.
[0143] The average length of the obtained composite fiber is preferably 0.1 to 500 mm, more preferably 0.1 to 7 mm, and the average diameter is preferably 0.001 to 2 mm, more preferably 0.005 to 0.5 mm. When the average length and average diameter are within the above ranges, there is no risk of the composite fibers being unnecessarily entangled with each other, and there is no risk of impairing good dispersibility. The aspect ratio is preferably 10 to 4,000, more preferably 50 to 2,000. The aspect ratio means the ratio of the major axis to the minor axis of the composite fiber.
[0144] Furthermore, in the obtained composite fiber, the ratio (A / B) of the length A of the cross section in the long axis direction in a cross section perpendicular to the long axis direction to the length B of the cross section in the short axis direction perpendicular to the long axis direction is preferably greater than 1, more preferably 1.5 or more, even more preferably 1.8 or more, and particularly preferably 2.0 or more. Moreover, the ratio A / B is preferably 20 or less, even more preferably 15 or less, and particularly preferably 10 or less. By keeping it in the above range, the wet performance is further improved. Note that, as long as A / B is greater than 1, the cross-sectional shape is not particularly limited, and may be any of elliptical, rectangular, polygonal, irregular, etc.
[0145] The blending amount of the composite fiber made of a hydrophilic resin having a coating layer formed thereon is preferably 0.1 to 100 parts by mass, more preferably 0.3 to 30 parts by mass, even more preferably 0.5 to 10 parts by mass, and even more preferably 1 to 6 parts by mass, based on 100 parts by mass of the rubber component. When the blending amount of the composite fiber made of a hydrophilic resin having a coating layer formed thereon is within the above range, it becomes possible to form cavities inside the composite fiber, exhibit good drainage properties, and maintain sufficient durability. Furthermore, the content ratio of the composite fiber and the void-introducing agent is not particularly limited, but from the viewpoint of achieving both abrasion resistance and wet performance and improving them, the mass ratio of the composite fiber and the void-introducing agent (void-introducing agent / composite fiber) is preferably 0.5 to 10, more preferably 1 to 8, even more preferably 1.5 to 7, and particularly preferably 2 to 6.
[0146] (Other Ingredients) In addition to the above-mentioned components, the rubber composition may contain compounding agents that are commonly used in the rubber industry as other components. As for the other components, for example, fillers other than the above-mentioned reinforcing fillers; organic peroxides; etc. may be further compounded. The content of these additives is not particularly limited and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, tire components, target performance, etc., and is preferably in the range of 0.1 to 200 parts by mass with respect to 100 parts by mass of the rubber component.
[0147] (Method of manufacturing vulcanized rubber composition for studless tires) The method for producing the vulcanized rubber composition for studless tires of the present invention is not particularly limited, but for example, the rubber composition can be produced by blending various components appropriately selected as necessary with the rubber component, and kneading, heating, extruding, etc. Then, the obtained rubber composition can be vulcanized to produce a vulcanized rubber.
[0148] The conditions for the kneading are not particularly limited, and various conditions such as the input volume of the kneading device, the rotation speed of the rotor, the ram pressure, the kneading temperature, the kneading time, the type of the kneading device, etc. can be appropriately selected depending on the purpose. Examples of the kneading device include a Banbury mixer, an intermix, a kneader, a roll, etc. that are usually used for kneading rubber compositions.
[0149] The conditions of the heat-in are not particularly limited, and various conditions such as the heat-in temperature, heat-in time, heat-in equipment, etc. can be appropriately selected depending on the purpose. Examples of the heat-in equipment include a heat-in roller machine usually used for heat-in of a rubber composition.
[0150] The extrusion conditions are not particularly limited, and various conditions such as extrusion time, extrusion speed, extrusion device, and extrusion temperature can be appropriately selected depending on the purpose. Examples of the extrusion device include an extruder that is usually used for extruding a rubber composition. The extrusion temperature can be appropriately determined.
[0151] The vulcanization apparatus, method, conditions, etc. are not particularly limited and can be appropriately selected according to the purpose. As the vulcanization apparatus, a molding vulcanizer using a mold used for vulcanizing a rubber composition can be mentioned. As the vulcanization condition, the temperature is, for example, about 100 to 190°C.
[0152] <Studless tires> The studless tire of the present invention is characterized by including the vulcanized rubber composition for studless tires of the present invention described above. By using the rubber composition, it is possible to achieve excellent wet performance and sustainability while maintaining good abrasion resistance. Here, the studless tire of the present invention can be used as, for example, a tire for a construction vehicle, a tire for a truck or a bus, a tire for an aircraft, or a tire for a passenger car, and is particularly preferably a tire for a passenger car or a tire for a truck or a bus, because the vulcanized rubber composition for a studless tire used as the material for the tread portion has excellent wet performance and abrasion resistance, and is advantageous when used as a tire for a passenger car or a tire for a truck or a bus.
[0153] When using the vulcanized rubber composition for studless tires of the present invention described above, for example, an unvulcanized rubber composition may be used for molding and then vulcanized, or a semi-vulcanized rubber that has been subjected to a pre-vulcanization step or the like may be used for molding and then further vulcanized. The tire of this embodiment is preferably a pneumatic tire, and the gas to be filled in the pneumatic tire may be normal air or air with an adjusted oxygen partial pressure, or an inert gas such as nitrogen, argon, or helium. EXAMPLES
[0154] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.
[0155] (Example 1, Comparative Example 1) A sample of the rubber composition of Comparative Example 1 was prepared by compounding and kneading in a conventional manner according to the composition shown in Table 1. In Table 1, each component is expressed as an integer or to one decimal place. Also, a sample of the rubber composition of Example 1 is prepared by compounding and kneading in a normal manner according to the formulation shown in Table 1. In Table 1, each component is expressed as an integer or to one decimal place. The other compounding ingredients each contain a specified amount of silica, sulfur, antioxidant, foaming agent, etc. For each sample obtained, the sustainability rate was calculated based on the composition of sustainable materials, as shown in Table 1.
[0156] [Table 1]
[0157] The results in Table 1 show that the rubber composition of Example 1 is expected to maintain the same processability and breaking strength as the rubber composition of Comparative Example 1, and that the sustainability rate can be improved, thereby contributing to reducing the environmental impact. [Industrial Applicability]
[0158] According to the present invention, it is possible to provide a vulcanized rubber composition for studless tires that can improve the wet performance and sustainable material ratio of a tire while maintaining good processability and workability of the rubber composition. Furthermore, according to the present invention, it is possible to provide a studless tire that has improved wet performance and sustainability rate while maintaining productivity and performance. [Explanation of symbols]
[0159] 10. Vulcanized rubber composition for studless tires 20 void
[0160] [Contribution to the United Nations-led Sustainable Development Goals (SDGs)] The SDGs have been proposed to realize a sustainable society. One embodiment of the present invention is considered to be a technology that can contribute to "No. 12_Responsible Consumption and Production" and "No. 13_Concrete measures against climate change."
Claims
1. A vulcanized rubber composition for studless tires, comprising: The natural rubber is a modified natural rubber having a nitrogen content of 0.1 to 0.3% by mass, The vulcanized rubber composition for studless tires is characterized in that it has a plurality of voids.
2. 2. The vulcanized rubber composition for studless tires according to claim 1, wherein the modified natural rubber is one in which proteins have been removed by a centrifugation process, an enzyme treatment, or a urea treatment.
3. 3. The vulcanized rubber composition for studless tires according to claim 1, wherein the modified natural rubber has a phosphorus content of more than 200 ppm.
4. The vulcanized rubber composition for studless tires according to claim 1 or 2, characterized in that the rubber composition further contains a reinforcing filler.
5. The vulcanized rubber composition for studless tires according to claim 1 or 2, wherein the rubber composition further comprises a void-introducing agent.
6. A studless tire comprising the vulcanized rubber composition for studless tires according to claim 1 or 2.
Citation Information
Patent Citations
Natural rubber and rubber composition using the same
JP2004262973A
Natural rubber, method of producing the same, rubber composition, and pneumatic tire using the composition
JP2010138359A